Deciphering cellular and molecular determinants of human DPCD protein in complex with RUVBL1/RUVBL2 AAA-ATPases. Issue 19 (15th October 2022) - Dos Santos Morais, Raphael; Santo, Paulo E.; Ley, Marie; Schelcher, Cédric; Abel, Yoann; Plassart, Laura; Deslignière, Evolène; Chagot, Marie-Eve; Quinternet, Marc; Paiva, Ana C.F.; Hessmann, Steve; Morellet, Nelly; et al.
Graphical abstract: Highlights: DPCD is a new RUVBL1/RUVBL2 cofactor. 3 DPCD interact with 1 RUVBL1/RUVBL2 heterohexamer with sub-micromolar affinity. DPCD regulates the oligomerization state of RUVBL1/RUVBL2 complex by disrupting the dodecameric state in nucleotide-dependent manner. DPCD binds DII domains of either RUVBL1 or RUVBL2. Abstract: DPCD is a protein that may play a role in cilia formation and whose absence leads to primary ciliary dyskinesia (PCD), a rare disease caused by impairment of ciliated cells. Except for high-throughput studies that identified DPCD as a possible RUVBL1 (R1) and RUVBL2 (R2) partner, no in-depth cellular, biochemical, and structural investigation involving DPCD have been reported so far. R1 and R2 proteins are ubiquitous highly conserved AAA + family ATPases that assemble and mature a plethora of macromolecular complexes and are pivotal in numerous cellular processes, especially by guaranteeing a co-chaperoning function within R2TP or R2TP-like machineries. In the present study, we identified DPCD as a new R1R2 partner in vivo . We show that DPCD interacts directly with R1 and R2 in vitro and in cells. We characterized the physico-chemical properties of DPCD in solution and built a 3D model of DPCD. In addition, we used a variety of orthogonal biophysical techniques including small-angle X-ray scattering, structural mass spectrometry and electron microscopy to assess the molecular determinants of DPCD interaction with R1R2. Interestingly, DPCD disrupts the dodecameric state of R1R2 complex upon binding and this interaction occurs mainly via the DII domains of R1R2.